CombiniJig ability in cucumber (Cucumis sativus)* - MUNSHI, A D; KUMAR, RAVINDER; PANDA, BISWAJIT (The Indian Journal of Agricultural Sciences, 2011)
A study was carried out during spring-summer seasons of 2000-2001 and 2001-2002 on the combining ability analysis in a 6x6 diallel cross of cucumber (Cucumis sativus L.) excluding reciprocals. The mean square due to general combing ability (gca) and specific combing ability (sea) were highly significant for almost all the characters indicating importance of both additive and non-additive genetic components ofvariation. specific combing ability component of variance was higher than general combing ability component ofvariance in all characters which indicated the importance of non-aoditive gene action for the control. Predictability ratio ar i average degree ofdominance observed to be less than 0.5 and more than 1 respectiyely for all the characters studied further confirmed the role ofnon-additive component of variance. The parents PI’ P2 and P4 were observed to be good combiners for number of characters including yield/plant. The crosses P4 x Ps’ P2 X Ps and P3 x P4 most pronlising cOInbinations for different characters including yield/plant. The results indicated the importance ofheterosis breeding for effective utilization ofnon-additive gene action .